Burkholderia cepacia meningitis in the Central African Republic - (:unkn) unknown (My University, 2019)
Burkholderia cepacia causes frequent infections in immunocompromised and hospitalized patients, with a significant mortality rate. This bacterial species has also been associated with epidemic outbreaks due to contamination of antiseptic solutions and parenteral and nebulized medications. In 2016, in the town of Bongonon in the north of the Central African Republic (CAR), a three-year-old boy with febrile meningeal syndrome (fever, neck stiffness and altered general condition) was admitted for a medical consultation provided by the nongovernmental organization MSF-Spain. On 20 March 2016, a sample of the boy's cerebrospinal fluid was sent to the Bacteriology Laboratory of the Pasteur Institute of Bangui for analysis. Conventional bacteriology showed that the isolate was a Gram-negative bacillus, which was identified as B. cepacia by using API 20 NE, with 99.9%confidence. In addition, the strain presented an acquired resistance to ticarcillin-clavulanate, ceftazidime and imipenem but remained susceptible to cotrimoxazole. As B. cepacia had never previously been isolated from cerebrospinal fluid in Africa, we chose to identify the strain by 16S rRNA gene sequencing. The molecular data showed that the isolate belonged to B. cepacia group. This is the first report of a case of meningitis caused by B. cepacia in CAR and developing countries.
Keywords: African Research